Magnetic Resonance Imaging of the Perineum in Pediatric Patients with Inflammatory Bowel Disease. (2013) - Jamieson, Douglas H; Shipman, Peter; Jacobson, Kevan
Abstract : Magnetic resonance imaging (MRI) has profoundly changed and improved the investigation of abdominal and pelvic inflammatory bowel disease (IBD) in pediatrics. Using an imaging modality without ionizing radiation is of particular advantage because the pediatric IBD population is young and often requires repeat evaluation. MRI of the pelvis has become the imaging gold standard for detecting and monitoring perianal disease while bowel-directed imaging techniques (eg, enterography, enteroclysis and colonography) can accurately evaluate bowel inflammation in IBD. With recent technological innovations leading to faster and higher resolution, the role of MRI in IBD will likely continue to expand. The present article focuses on MRI of the perineum in pediatric IBD.